Edukasi dan Praktik Prenatal Yoga sebagai Strategi Promotif Partisipatif untuk Mengurangi Nyeri Punggung Ibu Hamil Trimester II–III di Pademonegoro, Sidoarjo - Vindi Tyastutik; Nopri Padma Nudesti (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Back pain is a common musculoskeletal complaint among pregnant women, particularly in the second and third trimesters. This complaint is caused by anatomical and hormonal changes that occur during pregnancy. Given the negative impact that back pain can have on the comfort and quality of life of pregnant women, non-pharmacological interventions are an effective option. One approach that has proven beneficial is Prenatal Yoga, which can help reduce back pain and improve maternal comfort. This Community Service Program (KKN) aimed to improve the knowledge and skills of pregnant women in Pademonegoro Village, Sukodono District, Sidoarjo, in performing Prenatal Yoga movements as a participatory, promotive effort. The methods used in this activity included educational counseling, interactive discussions, and hands-on practice of safe yoga movements for pregnant women. This activity was designed to help pregnant women understand and apply yoga movements appropriate to their physical conditions during pregnancy. Evaluation conducted after the activity showed encouraging results. 85% of participants understood the material presented, while 90% were able to imitate the main Prenatal Yoga movements, namely the cat-cow pose and pelvic tilts. This second movement is known to be effective in reducing back tension and increasing body comfort. The evaluation results indicate that a practice-based educational approach can improve pregnant women's understanding and equip them with the skills to perform yoga independently at home. This program not only contributes to improving maternal health but also supports a promotive approach within the community. By providing the appropriate knowledge and skills, pregnant women can become more independent in maintaining their health during pregnancy, thereby improving their quality of life and supporting a smoother delivery.